2013
DOI: 10.1093/tropej/fmt071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drinking Water Fortification with Iron Plus Ascorbic Acid or Ascorbic Acid Alone in Daycare Centers as a Strategy to Control Iron-Deficiency Anemia and Iron Deficiency: A Randomized Blind Clinical Study

Abstract: Water fortification is efficient in controlling iron deficiency and anemia. Iron stores' recovery depends on a more effective offer of iron. Water fortification must be preceded by a careful assessment of the previous nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There are some studies in Asia regarding iodized water; however, as iodine has limited stability, this strategy is not always cost-effective [103]. Iron and ascorbic acid water fortification to prevent iron deficiency anaemia has been explored and, although successful, is still being researched [112,113].…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies in Asia regarding iodized water; however, as iodine has limited stability, this strategy is not always cost-effective [103]. Iron and ascorbic acid water fortification to prevent iron deficiency anaemia has been explored and, although successful, is still being researched [112,113].…”
Section: Discussionmentioning
confidence: 99%
“…Episodes of diarrhoea were reported by one study to be elevated in children receiving iron supplements along with zinc compared to children in the control groups (Richard et al 2006), but four interventions using other or no co-supplements contradicted this finding (Chang et al 2010;Chen et al, 2011;Richard et al, 2010;Moretti et al 2006). Four other studies (De Almeida et al 2014;Ekoe et al 2020;Andang'o et al 2007;Abizari et al 2012) reported explicitly that no "adverse effects" occurred under iron supplementation, without providing further details on which effects the authors addressed when interviewing the study participants.…”
Section: Adverse Gastrointestinal Effects In Childrenmentioning
confidence: 99%
“…The search for solutions to redress anemia has been explored in the region at the level of fortification of sugar, 20 milk, 21 and drinking water. 22 The Demographic and Health Surveys across the region are currently showing a reduction in anemia rates in young children and adult women.…”
Section: Where We Have Come In the Regionmentioning
confidence: 99%